2005
DOI: 10.1002/evan.20082
|View full text |Cite
|
Sign up to set email alerts
|

Children's Help and the Pace of Reproduction: Cooperative Breeding in Humans

Abstract: Because children's ability to support themselves falls below their consumption, human young are subsidized by others throughout much of their growth and development. Mothers, however, who often have multiple dependents of different ages, are faced with an allocation problem (Fig. 1). This has led to important debate about the evolution of a long period dependence and the development of nonmaternal strategies to provision young. This article focuses on the critical role that children themselves play. Because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
279
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(287 citation statements)
references
References 84 publications
2
279
0
6
Order By: Relevance
“…Unsolicited prosociality may serve to optimize the functioning of cooperative breeding systems (4,16). Humans are the only other primate besides callitrichids to have evolved features of cooperative breeding, such as infant care by grandmothers, older siblings, and fathers (4,44,45). Because only cooperatively breeding primates show such strong mutual interdependence (46), unsolicited prosociality in humans is likely to have arisen as our ancestors adopted extensive allomaternal care.…”
Section: Discussionmentioning
confidence: 99%
“…Unsolicited prosociality may serve to optimize the functioning of cooperative breeding systems (4,16). Humans are the only other primate besides callitrichids to have evolved features of cooperative breeding, such as infant care by grandmothers, older siblings, and fathers (4,44,45). Because only cooperatively breeding primates show such strong mutual interdependence (46), unsolicited prosociality in humans is likely to have arisen as our ancestors adopted extensive allomaternal care.…”
Section: Discussionmentioning
confidence: 99%
“…Because the intensive data demands of our analysis required more detailed individual information than was available, we drew a random subsample of women from the HDSS for a tailored survey. Our sample included even numbers of women from (i) the ICDDR,B Area and the Government Service Area, and (ii) each of three 15-y age categories (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and 50-64), allowing for better representation of older women and 45 y of time depth regarding fertility and its correlates. Our final survey sample size was 944 women.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Caldwell's Wealth Flows approach (19) suggests that in traditional agricultural societies, children provide their parents with significant wealth through labor, favoring high fertility, whereas in modern economies children consume wealth, resulting in low fertility. Other researchers have argued that children are always costly but that children's work can subsidize parental reproduction, leading to higher fertility (20,21).…”
Section: Demographic Transition Theorymentioning
confidence: 99%
“…Children may also relax their early dependence on parents by varying degrees through contribution to subsistence activities, including the direct care of younger siblings (see [46] for discussion of how subsistence type influences children's ability to help). However, in no population has it been demonstrated that children entirely offset their own energetic costs, implying that additional siblings will always dictate some division of family resources [7].…”
Section: (B) Socioecological Contextmentioning
confidence: 99%